Pelatihan Penggunaan Microsoft Office pada Ibu Kader PKK Desa Nglele Sumobito Guna Meningkatkan Keterampilan Pemanfaatan Teknologi - Muhammad Farid Nasrulloh; Muhammad Ansori Aris; Muhyiddin Zainul Arifin; Nana Nana; Munawarah Munawarah; Mohammad Faridl Darmawan (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The PKK of Nglele Village plays an important role in supporting family development and welfare through various work programs. In implementing these programs, PKK cadres are required to be able to manage administration, compile activity reports, and create accountability reports (LPJ) independently. The main problem faced by PKK cadres of Nglele Village is limited skills in operating Microsoft Word and Excel, so that the creation of accountability reports (LPJ) and administrative documents still depends on external parties. The Microsoft Office (Word and Excel) training program for PKK cadres of Nglele Village aims to: (1) Equip PKK cadres with basic Microsoft Word skills for document and report preparation. (2) Train PKK cadres in the use of Microsoft Excel for data processing and administrative recording. (3) Encourage PKK cadres' independence in compiling accountability reports (LPJ) without relying on external parties. Increase the effectiveness and efficiency of PKK cadres' work in carrying out organizational administration. The method applied in this training is a Hands-on Training-based Workshop combined with a Service Learning (SL) approach. Service Learning is a learning approach that integrates theory with real-world practice in the community. The conclusion of this community service activity is that it can increase the independence of PKK cadres, eliminating their reliance on external parties for administrative document management. This activity supports the capacity building of PKK cadres and empowers the Nglele Village community in the digital era, resulting in more structured, efficient, and professional work.